2023
DOI: 10.3390/brainsci13010142
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as Add-On Treatment in Psychotic Treatment-Resistant Depression

Abstract: Psychotic treatment-resistant depression is a complex and challenging manifestation of mood disorders in the clinical setting. Psychotic depression is a subtype of major depressive disorder characterized by mood-consistent hallucinations and/or delusions. Psychotic depression is often underdiagnosed and undertreated. Ketamine appears to have rapid and potent antidepressant effects in clinical studies, and the Federal Drug Agency approved the use of ketamine enantiomer esketamine-nasal spray for treatment-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…46 Wegielnik included patients with MDD and psychiatric illness or bipolar disorder and found that ketamine had good safety and efficacy for TRD patients with major depressive disorder and psychiatric comorbidity. 11 TRD with psychotic comorbidities was safe and well tolerated, consistent with previous results. 47 Based on the above studies, the safety of using ketamine for depression in specific populations also seems reasonable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…46 Wegielnik included patients with MDD and psychiatric illness or bipolar disorder and found that ketamine had good safety and efficacy for TRD patients with major depressive disorder and psychiatric comorbidity. 11 TRD with psychotic comorbidities was safe and well tolerated, consistent with previous results. 47 Based on the above studies, the safety of using ketamine for depression in specific populations also seems reasonable.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, esketamine was recently approved by the US Food and Drug Administration (FDA) for the acute management of MDD, depressive symptoms in adults with MDD with acute SI or behavior (MDSI), and as an adjunctive psychiatric indication for the treatment of MDD with a psychiatric emergency (MDD-PE). 10,11 Several RCTs and meta-analysis have reported that ketamine and esketamine have a good safety and tolerability profile in MDD or TRD, with rapid and effective antidepressant and anti-SI effects. [12][13][14] Given the findings of the above mentioned studies, there is growing interest in exploring whether ketamine and esketamine can be used to rescue patients with acute SI.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier study involving four patients with TRD-MDD-P who received ketamine as an adjunctive therapy, we demonstrated favorable safety and tolerance in terms of depressive and psychotic symptoms. We did not observe any exacerbation of psychotic symptoms during short- or long-term follow-up ( Gałuszko-Wȩgielnik et al, 2023 ).…”
Section: Discussionmentioning
confidence: 68%
“…Nevertheless, several studies have demonstrated that ketamine not only improves mood, but also reduces psychotic symptoms in patients with TRD who experience psychosis. The treatment shows good safety and tolerability ( da Frota Ribeiro et al, 2016 ; Pennybaker et al, 2017 ; Ajub and Lacerda, 2018 ; Kim et al, 2021 ; Veraart et al, 2021 ; Gałuszko-Wȩgielnik et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review ( 26 ) found that ketamine has a substantial antidepressant effect, although its effectiveness varies significantly across patients. Moreover, a recent study by Gałuszko-Węgielnik et al ( 108 ) found that ketamine is an effective add-on treatment to standard of care for people with treatment-resistant depression presenting psychotic features. Ketamine is administered as intravenous infusion and the subsequent monitoring revealed no exacerbation of psychotic symptoms in short and long-term observation, while stable remission and fast antisuicidal effect was found.…”
Section: Discussionmentioning
confidence: 99%